The Role of Political Activity in the Formation of Online Identity Bubbles - Koivula Aki; Kaakinen Markus; Oksanen Atte; Räsänen Pekka (John Wiley & Sons, Inc., 2022)
Increasing social media use has transformed political participation by creating social cliques and echo chambers, which involve interaction between like‐minded people. This article examines the relationship between online political activity and personal involvement in online identity bubbles. This study is the first to examine this phenomenon using nationally representative data; its data were derived from surveys targeted at 18–74‐year‐old Finns (N = 3,724). Measures included online political activity, the Identity Bubble Reinforcement Scale, and behavioral and demographic factors. The results show that online political activity was positively associated with online identity bubbles. This effect was strong even after controlling for behavioral and demographic factors. In addition to online political activity, general online activity, online network size, and basic sociodemographic background variables explained variation of involvement in online identity bubbles. However, neither political preference nor political interest had a systematic effect on involvement in these bubbles. The findings confirm the theoretical assumption that online bubbles can be captured using subjective survey measures. Political activity appears to be a key factor associated with the strength of the online bubble experience. This finding has significance in the contemporary information society, in which various mundane discussions and cultural disputes become politically tinged.